The complete astrological handbook for the twenty-first century : understanding and combining the wisdom of Chinese, Tibetan, Vedic, Arabian, Judaic, and Western astrology - Miller, Anistatia; Brown, Jared (New York Schocken, 1999)
A guide to reading the stars for the next century
D., 7/2000
Keywords: Astrology